Accounting: the teaching, the practice and what is missing. Issue 1 (3rd December 2020) - Rajeevan, Shanmugavel
Abstract : Purpose: This paper aims to identify the knowledge and practice gap in accounting education and propose an alternative teaching method to align accounting education to meet the needs of the practical world. Design/methodology/approach: A total of 500 questionnaires were circulated among four stakeholders (academics, accounting students, accountants in business and accountants in practice) and received an overall usable response rate of 27%. Findings: It was found that to reflect the current accounting practices, accounting students should be exposed to accounting specific experiential learning and industry specific training at an early stage of their academic education. Universities and professional institutes can work together to develop a curriculum to create an elite league of accounting professionals. Practical implications: The insights of this study would provide guidance to educators on how to develop an advance experiential learning structure for students that reflects the current accounting practices and technologies involved. Originality/value: This study contributes to the existing literature by means of providing an alternative teaching method for undergraduate accounting degree program.